Tom Randolph (Director of CGIAR Research Program on Livestock and Fish), on the Livestock and Fish CRP - Randolph, Thomas F. (International Livestock Research Institute, 2013)
Over 80 participants, including more than 35 Mission staff from 17 USAID Missions spent December 3-5 in Addis Ababa learning how to best advance their scaling strategies to achieve faster and deeper impact on Feed the Future goals through a Global Learning and Evidence Exchange (GLEE). Tom Randolph, Director of CGIAR Research Program on Livestock and Fish, presented on the Livestock and Fish CRP.